Cognition, personality, and stress in budgerigars, Melopsittacus undulatus. (25th September 2017) - Medina-García, Angela; Jawor, Jodie M; Wright, Timothy F
Abstract : Being shy or bold can determine success in intellectually challenging situations. We tested the relationships among personality, performance in several intellectually challenging tasks, and physiological stress in budgerigars. Personality determined the willingness of birds to participate in one task and problem-solving ability. Birds were either consistently unsuccessful or successful over time in most tasks. Being both consistently shy and unsuccessful in intellectually challenging situations could negatively impact survival and reproductive success. Abstract: To study the fitness effects of individual variation in cognitive traits, it is paramount to understand whether traits such as personality and physiological stress influence cognitive performance. We first tested whether budgerigars showed both consistent personalities and cognitive performance across time and tasks. We tested object and food neophobia, and exploratory behavior. We measured cognitive performance in habituation, ability to solve foraging problems, spatial memory, and seed discrimination tasks. Budgerigars showed consistency in their neophobic tendencies and these tendencies were associated with their exploratory behavior. Birds were also consistent in how they performed in most of the cognitive tasks (temporal consistency), but were not consistent in their performance across tasks (context consistency). Neither corticosterone levels (baseline and stress-induced) showed a significant relationship with either cognitive or personality measures. Neophobic and exploratory tendencies determined the willingness of birds to engage only in the seed discrimination task. Such tendencies also had a significant effect on problem-solving ability. Our results suggest that consistent individual differences in cognitive performance along with consistent differences in personality could determine response to environmental change and therefore have important fitness consequences.